2003
DOI: 10.1016/s0042-6989(03)00073-7
|View full text |Cite
|
Sign up to set email alerts
|

Blobs strengthen repetition but weaken symmetry

Abstract: The human visual system is more sensitive to symmetry than to repetition. According to the so-called holographic approach [J. Math. Psychol. 35 (1991) 151; Psychol. Rev. 103 (1996) 429; Psychol. Rev. 106 (1999) 622], however, this perceptual difference between symmetry and repetition depends strongly on spatial scaling. This was tested in three experiments, using symmetry and repetition stimuli that consisted of black and white patches, with patch size as the critical variable. In Experiment 1, patch size was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 18 publications
3
35
0
Order By: Relevance
“…Symmetry detection on the other hand has been considered by van der Helm [2] to have a holographic structure in which the number of elements is irrelevant. Supporting evidence for this proposition, using blob stimuli, was reported by Csatho, van der Vloed and van der Helm [29]. Additionally, Baylis and Driver [30], using line stimuli more like those in the present study, found that the speed of symmetry detection for the two sides of a single object is not influenced by the complexity of the reflected contour.…”
Section: Introductionsupporting
confidence: 90%
“…Symmetry detection on the other hand has been considered by van der Helm [2] to have a holographic structure in which the number of elements is irrelevant. Supporting evidence for this proposition, using blob stimuli, was reported by Csatho, van der Vloed and van der Helm [29]. Additionally, Baylis and Driver [30], using line stimuli more like those in the present study, found that the speed of symmetry detection for the two sides of a single object is not influenced by the complexity of the reflected contour.…”
Section: Introductionsupporting
confidence: 90%
“…For instance, qualitatively, the formal notion of holographic regularity seems to supply a perceptually relevant border between visual and nonvisual regularities [54], and also the holographic difference in structure between symmetry (point structure) and repetition (block structure) seems perceptually relevant [55]. Furthermore, the quantitative model W = E/N accounts for various perceptual differences between symmetry and repetition, including the fact that symmetry is better detectable than repetition, and it accounts for the detectability of symmetry in the presence of noise (for more details, see [21,26,49,51,56,57]). …”
Section: The Holographic Approachmentioning
confidence: 99%
“…The transparent holographic character of these regularities has shown to be relevant in human symmetry perception (21)(22)(23)(24). It also gave rise to the concept of ''hyperstrings'' that, in this article, is presented as a key to the computation of guaranteed simplest SIT codes.…”
mentioning
confidence: 92%
“…applied SIT to explain a variety of perceptual phenomena such as judged pattern complexity, pattern classification, neon effects, judged temporal order, assimilation and contrast, figure-ground organization, beauty, embeddedness, hierarchy, serial pattern segmentation and completion, and handedness. SIT started with a classification model, but nowadays it also contains comprehensive models of amodal completion (19,20) and symmetry perception (21)(22)(23)(24).…”
mentioning
confidence: 99%